Complications in Mandibular Midline Distraction. Issue 3 (September 2017) - de Gijt, Jan Pieter; Gül, Atilla; Wolvius, Eppo B.; van der Wal, Karel G.H.; Koudstaal, Maarten J.
Mandibular midline distraction (MMD) is a relatively new surgical technique for correction of transverse discrepancies of the mandible. This study assesses the amount and burden of complications in MMD. A retrospective cohort study was performed on patients who underwent MMD between 2002 and 2014. Patients with congenital deformities or a history of radiation therapy in the area of interest were excluded. Patient records were obtained and individually assessed for any complications. Complications were graded using the Clavien-Dindo classification system (CDS). Seventy-three patients were included of which 33 were males and 40 were females. The mean follow-up was 2.1 years. Twenty-nine patients had minor complications, grades I and II. Two patients had a grade IIIa and three patients had a grade IIIb complication. Common complications were pressure ulcers, dehiscence, and (transient) sensory disturbances of the mental nerve. This study shows that although MMD is a relatively safe method, complications can occur. Mostly the complications are mild, transient, and manageable without the need for any reoperation.